PENGARUH KEPEMIMPINAN KEPALA MADRASAH, KOMPETENSI GURU DAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA DI MI PERSIS RAHAYU KABUPATEN BANDUNG - Mulyana, Nurdin; Widaningsih, Sri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
This study aims to identify the influence of the Madrasa Principal, Teacher Competence, and Learning Media on student learning outcomes at MI Persis Rahayu, Bandung Regency. The research method used is a correlation study with a sample of 26 teachers at the madrasah. The research method used in this study is a survey method in which this method is part of a quantitative approach. The results of the study show that the principal of the madrasa has a great influence on student learning outcomes. In addition, Teacher Competence also has a large influence and Learning Media has a large influence on student learning outcomes. Furthermore, these three variables, namely the Madrasa Head, Teacher Competence, and Learning Media, have a large influence together. The results of this study make an important contribution in understanding the factors that influence student learning outcomes in madrasas and can be used as a guide for improving the quality of education in these educational institutions.